An Insight of Scientific Developments in TSC for Better Therapeutic Strategy - Natarajan, Nalini; Thiruvenkatam, Vijay (Current topics in medicinal chemistry, 2020)
Tuberous sclerosis complex (TSC) is a rare genetic disease, which is characterized by noncancerous tumors in multi-organ systems in the body. Mutations in the TSC1 or TSC2 genes are known to cause the disease. The resultant mutant proteins TSC1 (hamartin) and TSC2 (tuberin) complex evade its normal tumor suppressor function, which leads to abnormal cell growth and proliferation. Both TSC1 and TSC2 are involved in several protein-protein interactions, which play a significant role in maintaining cellular homeostasis. The recent biochemical, genetic, structural biology, clinical and drug discovery advancements on TSC give a useful insight into the disease as well as the molecular aspects of TSC1 and TSC2. The complex nature of TSC disease, a wide range of manifestations, mosaicism and several other factors limits the treatment choices. This review is a compilation of the course of TSC, starting from its discovery to the current findings that would take us a step ahead in finding a cure for TSC.